2018
DOI: 10.1002/cam4.1578
|View full text |Cite
|
Sign up to set email alerts
|

Overactivated neddylation pathway in human hepatocellular carcinoma

Abstract: Dysregulation of the neddylation pathway is related to various cancers. However, the specific role of the neddylation pathway in human hepatocellular carcinoma (HCC) remains largely unclear. In this study, the neddylation pathway in HCC and adjacent noncancerous liver (ANL) tissues was evaluated by immunohistochemistry (IHC), Western blotting, and qRT‐PCR (quantitative real‐time polymerase chain reaction). The results showed that the entire neddylation pathway, including NEDD8 (the IHC staining of NEDD8 repres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 35 publications
(74 reference statements)
3
29
0
Order By: Relevance
“…Thus, metastatic HCC samples showed significantly higher SREBP‐1 and UBC12 levels in the GEO dataset analysis. Our finding is in line with the observation that UBC12 levels were increased in certain cancers including HCC 36 . In our assays, UBC12 and SREBP‐1 levels were both enhanced in HCC, confirming the positive correlation.…”
Section: Discussionsupporting
confidence: 91%
“…Thus, metastatic HCC samples showed significantly higher SREBP‐1 and UBC12 levels in the GEO dataset analysis. Our finding is in line with the observation that UBC12 levels were increased in certain cancers including HCC 36 . In our assays, UBC12 and SREBP‐1 levels were both enhanced in HCC, confirming the positive correlation.…”
Section: Discussionsupporting
confidence: 91%
“…As an example it has been shown that high expression of RBX1 is coupled to poor prognosis in gastric cancer [25], bladder cancer [26], and non-small cell lung cancer [27]. Similarly, NEDD8 overexpression has been coupled to poor prognosis in hepatocellular carcinoma [28] and bladder cancer [29], and increased levels of neddylated Cullin-1 has previously been shown in high-grade lung NETs [30]. Also in nasopharyngeal carcinoma, overexpression of NEDD8 was coupled to shorter overall survival [31] and in the same publication it was also shown in cell line models that suppression of NEDD8 levels directly inhibits cell growth.…”
Section: Discussionmentioning
confidence: 99%
“…116 The NEDD8-mediated down-regulation of SRSF3 bears relevance to HCC because multiple components of the neddylation machinery are upregulated and correlate with shorter survival in HCC patients. 117 SRSF2, unlike SRSF3, is up-regulated in HCC and correlates with poor prognosis in patients. 111 Previous work has shown that Srsf2 is essential for liver homeostasis and survival because liver-specific deletion of Srsf2 in mice caused liver failure and death within the first 2-4 weeks.…”
Section: Srsf Rna Binding Proteins Differentially Regulate Hepatic Gementioning
confidence: 94%